Container transport - Shilimov M. V., Ulyanina L. Y. (Science in figures, 2017)
the researchers of the article discuss basic information on the TRANS-Siberian railway, variety of containers and their main advantages and disadvantages.
Keywords: контейнерные перевозки; классификация контейнерных перевозок; преимущества контейнерных перевозок; container transportation; classification of container transport; benefits of container transport